Методическое обеспечение испытаний (тестов) Всероссийского физкультурно-спортивного комплекса «Готов к труду и обороне» - Grigoreva E. L., Zhemchug I. S., Griaznov I. I., Lebedkina M. V. (Innovative technologies in science and education, 2017)
In this article it is discussed questions of implementation of standards of a sports and sports complex (GTO) "It is ready to work and defense". Need of development of a methodical complex to implementation of standards of GTO is proved.
Keywords: Всероссийский физкультурно-спортивный комплекс; подготовка; спортивно-физкультурная программа; выполнение тестовых нормативов